The Calcium-Looping technology for CO2 capture: On the important roles of energy integration and sorbent behavior. (15th January 2016) - Perejón, Antonio; Romeo, Luis M.; Lara, Yolanda; Lisbona, Pilar; Martínez, Ana; Valverde, Jose Manuel
Highlights: The Calcium Looping (CaL) technology is a potentially low cost and highly efficient postcombustion CO2 capture technology. Energy integration and sorbent behavior play a relevant role on the process. The industrial competitiveness of the process depends critically on the minimization of energy penalties. It may be used in precombustion capture systems and other industrial processes such as cement production. Sorbent deactivation must be assessed under realistic conditions involving high CO2 concentration in the calciner. Abstract: The Calcium Looping (CaL) technology, based on the multicyclic carbonation/calcination of CaO in gas–solid fluidized bed reactors at high temperature, has emerged in the last years as a potentially low cost technology for CO2 capture. In this manuscript a critical review is made on the important roles of energy integration and sorbent behavior in the process efficiency. Firstly, the strategies proposed to reduce the energy demand by internal integration are discussed as well as process modifications aimed at optimizing the overall efficiency by means of external integration. The most important benefit of the high temperature CaL cycles is the possibility of using high temperature streams that could reduce significantly the energy penalty associated to CO2 capture. The application of the CaL technology in precombustion capture systems and energy integration, and the coupling of the CaL technology with other industrial processes are also described. In particular, the CaL technology has a significant potential to be a feasible CO2 capture system for cement plants. A precise knowledge of the multicyclic CO2 capture behavior of the sorbent at the CaL conditions to be expected in practice is of great relevance in order to predict a realistic capture efficiency and energy penalty from process simulations. The second part of this manuscript will be devoted to this issue. Particular emphasis is put on the behavior of natural limestone and dolomite, which would be the only practical choices for the technology to meet its main goal of reducing CO2 capture costs. Under CaL calcination conditions for CO2 capture (necessarily implying high CO2 concentration in the calciner), dolomite seems to be a better alternative to limestone as CaO precursor. The proposed techniques of recarbonation and thermal/mechanical pretreatments to reactivate the sorbent and accelerate calcination will be the final subjects of this review.